MODELLING OF ACTIVITY OF OPERATORS OF THE DIAGNOSTIC EQUIPMENT OF THE MOTOR TRANSPORTATION ENTERPRISES - V. E. Ovsyannikov; V. I. Vasilyev (Вестник СибАДИ)
In this article questions of modeling of activity of operators of the diagnostic equipment of the enterprises of a motor transportation complex are considered. The analysis of the main aspects which cause specifics of the choice like model is carried out. It is established that application of imitating models is the most rational. The imitating model allowing to realize algorithms of activity of operators with any values of psychological tension at an equipment design stage is developed.